Our first experience with Integra - Tymonová, Jarmila; Adámková, Monika; Klosová, H; Kadlčík, Michal; Zámečníková, I (Acta chirurgiae plasticae (English ed.), 2005)
The advantages of Integra have lead to an increase in its use after extensive burn injuries, in reconstructive surgery after burns, and abroad in general reconstructive surgery as well. At the Burn Center of FNsP Hospital in Ostrava Integra was used for the first time in March 2003. Since then, seven patients have undergone operations, involving the use of Integra in 14 body areas. In four of the patients scars after burns were corrected – on the neck, axilla, two on the trunk, two in the popliteal area and one between the toes. In three patients the artificial skin was applied after necronectomy. In a 7-month-old baby and in a 2-year-old child with burn injuries exceeding 25% of the body surface it was applied twice on the trunk, once on the upper extremity and once on the lower extremity. In an adult female Integra was applied on her neck and axilla after burns to a lesser extent.We have evaluated the scars one year after surgery in two patients. Cosmetic appearance was good in both of them.We have noted good functional result after the reconstruction of axilla. After reconstruction in the neck area and reconstruction of the necrectomy in the neck area and axilla, the functional results were average. The average functional results in both patients are probably due to poor compliance with the immobilization and following rehabilitation program.
Keywords: Skin, Artificial; Plastic Surgery Procedures; lidé; popálení; Burns; umělá kůže; zákroky plastické chirurgie; Humans